BAITUL MAL MANAGEMENT IN SOCIAL AND ECONOMIC SUPPORT FOR THE ACEH COMMUNITY (Lex localis - Journal of Local Self-Government, 2025)
Baitul Mal is an Islamic financial institution whose objective is to distribute wealth to the needy and its management faces many challenges in the modern economic and social context. This study aims to identify the major challenges faced in contemporary management of Baitul Mal. This study used descriptive analysis to evaluate literature and related data, and conducted interviews with Baitul Mal managers, indigenous communities, and entrepreneurship experts. Research shows that one of the biggest challenges in solving the Baitul Mal problem is the imbalance between economic growth and wealth distribution. In a modern economic context that often leads to greater social inequality, Baitul Mal's management often struggles to ensure fair and equitable distribution. In addition, economic globalization is also a factor complicating the management of Baitul Mal. The integration of global markets has expanded the scope of financial transactions and requires more complex management strategies to ensure compliance with Islamic principles in an increasingly globally interconnected context. Other challenges include demographic changes, with increasing and diverse populations making it difficult to identify and meet diverse needs. At the same time, technological changes have also impacted the way Baitul Mal is managed, requiring the adoption of more advanced information and communication technologies to increase efficiency and transparency. In short, the management of Baitul Mal faces complex and diverse challenges in the modern economic and social era. Addressing these challenges requires a comprehensive and innovative approach that takes into account Islamic principles and the changing needs of society.